Cover Feature: Photo‐Induced Assembly of a Luminescent Tetraruthenium Square (Chem. Eur. J. 65/2017). Issue 65 (18th September 2017) - Laramée‐Milette, Baptiste; Nastasi, Francesco; Puntoriero, Fausto; Campagna, Sebastiano; Hanan, Garry S.
Abstract : Self‐assembly is a powerful synthetic tool that has led to the development of one‐, two‐ and three‐dimensional architectures. Herein a strategy for the construction and de‐construction of a supramolecular structure through light‐induced assembly and dis‐assembly is described. These results open the way to a new avenue in supramolecular chemistry, leading to the preparation of structurally‐organized assemblies by photochemical techniques. More information can be found in the Full Paper by G. S. Hanan et al. onpage 16497 .